“Efecto del número de aporques en maíz variedad marginal 28-T en la provincia de San Martín” - Mercado Aguilar, Rocio Lluliana (2012)
This research paper entitled "Effect of number of hilling corn variety Marginal 28- Tropical in the province of San Martin", was conducted in order to study and evaluate the effect of number of hilling on performance and production and determine maize production costs. We used the statistical design of randomized complete block (RCBD). The results indicate that the yield of treatments with ridging exceeded more than 19.9%, 11.9% and 1O.7% for treatments T2 (1 hilling 25 DOS), T3 (2 hilling DOS 25 and 35), and T4 (3 hilling 25, 35 and 45 DOS), without hilling treatment, highlighting the influence on the biometric characteristics of the ear, thus determining its effect on performance. The hilling hilling and determined the number of direct influences on the biometric characteristics of the ear as ear weight, length and ear diameter, kernels per row and 100 seed weight, expressed variables that affect performance. The number of harvested plants, days to 50% of male and female flowering, ear height and the total number of ears harvested, were not affected by the effect of hilling. Treatment T1 (control-without hilling) was the most susceptible to a root lodging of 1 O plants and six plants with stalk lodging, showing that avoids lying hilling and increases space for root development, allowing ensure higher productivity of grain maize cultivatíon. Key words: Marginal 28 Tropical, performance, treatments, replications, variables, lodging, witness, male and female flowering.